2004
DOI: 10.1017/s1041610204000468
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the association between the Behavioral and Psychological Symptoms of Dementia and burden of care

Abstract: Background: Several reports have indicated that the Behavioral and Psychological Symptoms of Dementia (BPSD) are associated with increased burden of care, carer depression and increased rates of institutionalization of patients. The present study aims to review the association between these variables in cross-sectional as well as longitudinal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
210
3
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(232 citation statements)
references
References 60 publications
6
210
3
8
Order By: Relevance
“…They find overall evidence that behavioral problems (e.g., disruptive and aggressive behavior), physical and cognitive impairment, and the time spent on caregiving place a burden on the caregiver and increase symptoms of depression, with behavioral problems being particularly important when caring for demented care 23 recipients. This finding is supported by Black and Almeida's (2004) review of associations between behavioral and psychological symptoms of dementia and the burden on caregivers.…”
Section: Psychological Healthsupporting
confidence: 53%
“…They find overall evidence that behavioral problems (e.g., disruptive and aggressive behavior), physical and cognitive impairment, and the time spent on caregiving place a burden on the caregiver and increase symptoms of depression, with behavioral problems being particularly important when caring for demented care 23 recipients. This finding is supported by Black and Almeida's (2004) review of associations between behavioral and psychological symptoms of dementia and the burden on caregivers.…”
Section: Psychological Healthsupporting
confidence: 53%
“…A tradition of managing behavior pharmacologically may be an explanation. It is not surprising that imposed mental workload correlated with antipsychotic medication, as such a correlation has previously been shown between staff workload and behavioral problems (Black and Almeida, 2004). All these four associated factors, however, raise the question of whether the patients are treated for their own sake, or for that of the staff.…”
Section: Discussionmentioning
confidence: 98%
“…Some of the symptoms increase the difficulty of caring for the person with dementia, and there is a correlation between BPSD and burden of care, and even with caregiver depression (Black and Almeida, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Others have found that subjective caregiver perceptions of problems, satisfaction with and amount of social support, available resources, coping skills, and feelings of self-efficacy are important predictors of caregiver depression and stress [20,21]. Similarly, there is evidence that subjective caregiver factors may be more important than patient factors to the prediction of nursing home placement [22,23].Caregivers who were high in burden reported several areas of family dysfunction that distinguished them from those caregivers low in burden. We found that burden was associated with perceived ineffective communication among family members.…”
mentioning
confidence: 99%